Quality of life in patients with uveitis: data from the ULISSE study (Uveitis: cLInical and medico-economic evaluation of a Standardised Strategy for the Etiological diagnosis). Issue 7 (24th July 2020) - Bertrand, Pierre-jean; Jamilloux, Yvan; Kodjikian, Laurent; Errera, Marie-Helene; Perard, Laurent; Pugnet, Gregory; Tieulie, Nathalie; Andre, Marc; Bielefeld, Philip; Bron, Alain M; Decullier, Evelyne; Bin, Sylvie; et al.
Abstract : Aims: To assess vision-related (VR-QOL) and health-related quality of life (HR-QOL) in a large series of patients with de novo uveitis at baseline and 6-month follow-up. Methods: Non-inferiority, prospective, multicentre, cluster randomised controlled trial registered under the Unique Identifier: NCT01162070 . VR-QOL and HR-QOL were assessed by the 25-item National Eye Institute Visual Function Questionnaire (VFQ-25) and the Medical Outcomes Study 36-item Short Form Survey (SF-36). Results: At inclusion, 466 patients completed the VFQ-25. The mean composite score was 80.0 (±16.7). In multivariate analysis, higher age, female sex and insidious onset were significantly associated with lower QOL. At 6 months, 138 patients completed the VFQ-25, with a significantly higher mean composite score of 82.6 (±16.7). SF-36 mental component was 42.9 (±11.3) and physical component was 47.2 (±8.5) at inclusion (n=425). HR-QOL improvement at 6 months was not clinically significant. Conclusion: QOL seems relatively well preserved in this cohort; only VR-QOL improved significantly at 6 months, especially in patients with low initial visual acuity.